Implementing SAP for manage financial and accounting at PT Pegadaian Kantor Wilayah Provinsi Jawa Timur: Menerapkan SAP untuk mengelola keuangan dan akuntansi di PT Pegadaian Kantor Wilayah Provinsi Jawa Timur - Muhammad Vega Putra Lakarupu; Yuniningsih (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
System implementation review activities of the SAP (System Application and Product in Data Processing) system within the Finance Department of PT Pegadaian, East Java Regional Office, as part of the company's digital transformation efforts. SAP is utilized to enhance the effectiveness of financial data management, including transaction recording, tax processing, and real-time reporting. Using a qualitative descriptive method and direct observation during an internship program, the study presents an in-depth overview of both the benefits and challenges of SAP usage. The findings indicate that SAP significantly improves work efficiency and data accuracy, although technical issues such as data loss due to unstable internet connections still occur. Therefore, maintaining a reliable internet network is essential for optimizing the system’s performance. These insights may serve as a reference for other institutions aiming to adopt digital financial information systems.